2022
DOI: 10.1180/clm.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Study of the adsorption mechanisms of NH3, H2S and SO2 on sepiolite using molecular dynamics simulations

Abstract: This is a 'preproof' accepted article for Clay Minerals. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Brigatti et al (1996) stated that heavy metal cation sorption can occur at the surface of broken edges, in channels and at specific sites of sepiolite according to crystal-chemical affinity. The adsorption of NH 3 , H 2 S and SO 2 (Zhou et al, 2023), ethylene gas (Erdoğan & Esenli, 2021), phenanthrene (González-Santamaría et al, 2017), Ni 2+ ions (Kıpçak et al, 2020) and red dye (Çoruh et al, 2011) on sepiolite have also been reported previously.…”
mentioning
confidence: 65%
“…Brigatti et al (1996) stated that heavy metal cation sorption can occur at the surface of broken edges, in channels and at specific sites of sepiolite according to crystal-chemical affinity. The adsorption of NH 3 , H 2 S and SO 2 (Zhou et al, 2023), ethylene gas (Erdoğan & Esenli, 2021), phenanthrene (González-Santamaría et al, 2017), Ni 2+ ions (Kıpçak et al, 2020) and red dye (Çoruh et al, 2011) on sepiolite have also been reported previously.…”
mentioning
confidence: 65%
“…Sepiolite is an abundant, natural and nontoxic phyllosilicate with a compositional formula of Mg 8 Si 12 O 30 (OH 2 ) 4 •8H 2 O [1,2]. The structure of sepiolite contains extended silicon-oxygen sheets, making it a layered silicate mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Camara et al (2019) found through MD simulation that poly(N-vinyl caprolactam) (PNVCL) had an excellent swelling-inhibitory ability for Na-montmorillonite (Mnt) by hindering the migration of interlayer particles, and these authors predicted the stability of PNVCL's response at high temperatures. Zhou et al (2022) found that sepiolite-adsorption capacities for gases decreased in the order SO 2 > H 2 S > NH 3 , and the diffusion coefficients were affected by the number of gas/water molecules. Parameters such as diffusion coefficient and atomic residence time have been calculated by Peng et al (2020), demonstrating that NH 4+ remains for longer than Na + on the hexagonal pores on the surface of Mnt, forming a more stable hydration layer under low-hydration conditions.…”
mentioning
confidence: 99%